2012
DOI: 10.5194/acpd-12-5425-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modelling of organic aerosols over Europe (2002–2007) using a volatility basis set (VBS) framework with application of different assumptions regarding the formation of secondary organic aerosol

Abstract: A new organic aerosol (OA) module has been implemented into the EMEP chemical transport model. Four different volatility basis set (VBS) schemes have been tested in long-term simulations for Europe, covering the six years 2002–2007. Different assumptions regarding partitioning of primary OA (POA) and aging of POA and secondary OA (SOA), have been explored. Model results are compared to filter measurements, AMS-data and source-apportionment studies, as well as to other model studies. The present study ind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
0
22
0
1
Order By: Relevance
“…Bergstrom et al (2012) found that a VBS model reproduced observed OA concentrations over Europe in summer reasonably well. Matsui et al (2014) reported that OA concentrations were better reproduced by a VBS model in western Japan and the TMA because the model included SVOC aging processes.…”
Section: Comparison Of Model Performance With That Of Other Modelsmentioning
confidence: 78%
See 1 more Smart Citation
“…Bergstrom et al (2012) found that a VBS model reproduced observed OA concentrations over Europe in summer reasonably well. Matsui et al (2014) reported that OA concentrations were better reproduced by a VBS model in western Japan and the TMA because the model included SVOC aging processes.…”
Section: Comparison Of Model Performance With That Of Other Modelsmentioning
confidence: 78%
“…Recently, a volatility basis set (VBS) model that can deal with direct emissions of semivolatile and intermediate-volatility organic compounds (SVOCs and IVOCs, respectively), with the oxidation of these compounds, and with SVOC aging was developed (Donahue et al, 2006;Robinson et al, 2007). The VBS model has been widely used in the United States (Lane et al, 2008;Murphy and Pandis, 2009;Tessum et al, 2015), Europe (Bergstrom et al, 2012;, and Asia (Matsui et al, 2014;Han et al, 2015;Morino et al, 2015), and has improved simulations of OA concentrations. Morino et al (2014) compared the results obtained with five SOA models over the TMA and found that the VBS model reproduced the observed SOA concentrations well, whereas other models, including SOA yield models, underestimated SOA.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in more detail in Bergström et al (2011), the model performance varies between stations. It seems clear that the VBS-PAPS version overestimates OC in summer at most locations.…”
Section: Appendix Dmentioning
confidence: 99%
“…(see Sect. 3.1, Johansson et al, 2008;Denier van der Gon et al, 2011). The particle number emissions in Europe are dominated by sub-micron particles.…”
Section: E1 In-situ Formation (Nucleation) Of Aerosolsmentioning
confidence: 99%
“…Cette thèse ouvre la voie à de nouvelles améliorations pouvant être apportées aux émissions de précurseurs gazeux d'AOS pris en compte dans les modèles. La procédure d'agrégation mise en application au cours de cette thèse est fondée sur un inventaire d'émission américain datant des années 1990 Bergström et al (2012) ont rapporté que lorsque les AOP émis sont partitionnés entre les phases gazeuse et particulaire et distribués entre les différentes classes de volatilité, les concentrations en aérosols organiques simulées sont plus élevées et en meilleur accord avec les observations. La prise en compte de la volatilité et du vieillissement chimique des AOP dans la paramétrisation VBS utilisée dans le cadre de cette thèse permettrait de décrire de manière plus réaliste les propriétés de l'aérosol organique et probablement de simuler des concentrations en aérosols organiques plus proches des observations.…”
Section: # $unclassified